Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3390/w5020593
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Decentralized Rainwater Management in Urban Planning and Design: Flood Resilient and Sustainable Water Management Using the Example of Coastal Cities in The Netherlands and Taiwan

Abstract: Urbanized delta areas worldwide share a growing tendency of exposure to water stress induced by the effects of climate change and anthropogenic factors, threatening the operation of infrastructure systems and future urban development. The important synergistic impacts coexisting with freshwater scarcity are increasing urbanization rates, subsiding soils, saltwater intrusion in aquifers and rivers, coastal erosion, and increased flooding. Innovative design strategies and concepts for the integration of decentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A key debate within this work is the question of whether centralized, decentralized or hybrid systems (both physical and institutional) are more likely to contribute to increased resilience and what that might look like in practice. Modeling studies have demonstrated that decentralized rainwater management, including retention, storage, and reuse strategies that are integrated into spatial planning and urban design, can reduce flood risks while simultaneously enhancing freshwater availability (Schuetze & Chelleri, ). Others promote hybrid approaches drawing on both centralized and decentralized models.…”
Section: Discussionmentioning
confidence: 99%
“…A key debate within this work is the question of whether centralized, decentralized or hybrid systems (both physical and institutional) are more likely to contribute to increased resilience and what that might look like in practice. Modeling studies have demonstrated that decentralized rainwater management, including retention, storage, and reuse strategies that are integrated into spatial planning and urban design, can reduce flood risks while simultaneously enhancing freshwater availability (Schuetze & Chelleri, ). Others promote hybrid approaches drawing on both centralized and decentralized models.…”
Section: Discussionmentioning
confidence: 99%
“…DRWH systems are mainly implemented at a building scale. Various methods exist for calculating water savings and for designing the storage capacity of buildings by setting up DRWH systems [7,[11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The decentralized water management systems integrated in the conversion design were based on the new and innovative approaches for the reconstruction of the natural water and nutrient cycle. Rainfall on the IC is managed onsite, including the harvesting, retention, infiltration storage and utilization of rainwater [23][24][25][26]. Wastewater and organic waste produced in the converted IC design is managed and recycled onsite with decentralized technologies and systems.…”
Section: Sustainable Urban Regeneration Framework For the Renovationmentioning
confidence: 99%